2015
DOI: 10.1002/jcp.24972
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Runx2, induced by cyclic mechanical tension via ERK1/2 pathway, contributes to osteodifferentiation of human periodontal ligament fibroblasts

Abstract: Occlusal force is an important stimulus for maintaining periodontal homeostasis. This is attributed to the quality of human periodontal ligament fibroblasts (hPDLFs) that could transfer occlusal force into biological signals modulating osteoblst differentiation. However, few studies investigated the mechanism of occlusal force-induced osteodifferentiation of hPDLFs. In our study, we used the cyclic mechanical tension (CMT) at 10% elongation with 0.5 Hz to mimic occlusal force, and explored its effects on osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 54 publications
1
45
0
Order By: Relevance
“…In this study, upregulation of osteogenic gene expression was observed in cells under continuous tensile strain (Li et al, 2014; Ren et al, 2015; Shen et al, 2014; Tang et al, 2014; Wei et al, 2008; Zhang et al, 2015). Animal experiments have demonstrated that continuous tensile strain generated by orthodontic appliances also upregulates osteogenic markers in PDL during orthodontic tooth movement (Kawarizadeh et al, 2005; Kim et al, 2012; Watanabe et al, 2008).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, upregulation of osteogenic gene expression was observed in cells under continuous tensile strain (Li et al, 2014; Ren et al, 2015; Shen et al, 2014; Tang et al, 2014; Wei et al, 2008; Zhang et al, 2015). Animal experiments have demonstrated that continuous tensile strain generated by orthodontic appliances also upregulates osteogenic markers in PDL during orthodontic tooth movement (Kawarizadeh et al, 2005; Kim et al, 2012; Watanabe et al, 2008).…”
Section: Discussionmentioning
confidence: 54%
“…Numerous studies have shown that mechanical strain induces osteogenic differentiation of PDL cells by increasing osteogenic genes such as RUNX2 and OPN (Li et al, 2014; Ren et al, 2015; Tang et al, 2014; Zhang et al, 2015). Therefore, we investigated the effects of continuous tensile strain from the device on the osteogenic gene expression in HPL cells.…”
Section: Resultsmentioning
confidence: 99%
“…12% deformation was selected according to the results from a finite element model, which predicts the deformation of PDLCs (human maxillary central incisor, mid‐root level) subjected to horizontal displacements under physiological loading conditions . Although currently there is no consensus about the loading conditions such as stress type, magnitude, frequency, and duration that best represent the force loading on periodontal ligament during OTM, the strain application system and the parameters adopted in our study have been frequently used and validated to promote osteogenic differentiation of PDLCs in previous studies …”
Section: Discussionmentioning
confidence: 99%
“…In the tension side of the OTM, new bone forms as a result of tensile strain on the PDLCs. Accordingly, the expressions of osteogenic markers in PDLCs, such as core‐binding factor α1 (Cbfα1, also known as RUNX2), osterix (OSX), osteocalcin (OCN), collagen type I (COL I), and alkaline phosphatase (ALP), are found to be elevated under tensile strain, suggesting an osteoblastic phenotype of PDLCs …”
Section: Introductionmentioning
confidence: 99%
“…[11] In periodontal ligament stem cells, Ren et al demonstrated that cyclic mechanical tension mimicking occlusal force resulted in increased osteogenic differentiation via ERK1/2-mediated runt-related transcription factor 2 (Runx2) activation. [12] …”
Section: Introductionmentioning
confidence: 99%